An Association of Beliefs in Divine Intervention and Moral Foundations - Dumais, Travis (The international journal of religion and spirituality in society, 2015)
Converging lines of evidence suggest that belief in divine intervention is associated with pro- social/moral behavior. The present study tests the hypothesis that one's belief in divine intervention will predict willingness to commit a subset of moral violations that emphasize group commitment. Via an internet survey, participants (N=201) responded to the Moral Foundations of Sacredness Questionnaire (assessing Individualistic and Binding sacred values) and a modified God Intervention Scale (Divine Intervention Scale). Separate correlation analyses for religious, agnostic, and atheist individuals showed significant positive correlations among three of the five moral foundation scales (loyalty, authority, and purity) and the measure of divine intervention for the religious group only. In addition, a comparison of the three groups revealed significant differences on three moral foundation sub-scales that comprise the binding foundation measure. Results support the notion that belief in an intervening Divinity is associated with reduced likelihood to commit moral violations, especially violations in the domains of loyalty, authority, and purity.